2019
DOI: 10.1097/md.0000000000016794
|View full text |Cite
|
Sign up to set email alerts
|

Emotional problems in mothers of autistic children and their correlation with socioeconomic status and the children's core symptoms

Abstract: To investigate the emotional problems (depressive and anxiety symptoms) of mothers of children with autism spectrum disorder (ASD) and explore the role of the mother's socioeconomic status (SES) and the core symptoms of the child on the mother's emotional problems. This cross-sectional survey was performed in 180 mothers of children with ASD in Chang Sha city of China. The 7-item Generalized Anxiety Disorder Scale (GAD-7) and the 9-item Patient Health Questionnaire (PHQ-9) were used to assess the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 41 publications
(47 reference statements)
3
18
0
2
Order By: Relevance
“…Similar results were found for models predicting anxious symptoms, with psychological inflexibility emerging as the greatest predictor of anxious symptomatology. Challenging parenting experiences also predicted anxiety in mothers of children with ASD, which is congruent with previous findings that children's core ASD symptoms (Zhou et al, 2019) and behavioural problems and parental self-efficacy (Hastings & Brown, 2002) are all associated with anxiety in mothers of children with ASD. Results further showed that psychological inflexibility and challenging parenting experiences partially mediated the relationship between BAP and anxiety in mothers of children with ASD, extending previous findings (Lau et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were found for models predicting anxious symptoms, with psychological inflexibility emerging as the greatest predictor of anxious symptomatology. Challenging parenting experiences also predicted anxiety in mothers of children with ASD, which is congruent with previous findings that children's core ASD symptoms (Zhou et al, 2019) and behavioural problems and parental self-efficacy (Hastings & Brown, 2002) are all associated with anxiety in mothers of children with ASD. Results further showed that psychological inflexibility and challenging parenting experiences partially mediated the relationship between BAP and anxiety in mothers of children with ASD, extending previous findings (Lau et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…It was also not possible to confirm children's ASD diagnoses due to the anonymous online nature of the study. Furthermore, the regression models did not include a discrete measure of children's symptom severity, which has previously been found to be associated with maternal mental health (Benson, 2006;Benson & Karlof, 2009;Miranda et al, 2019;Zhou et al, 2019). Finally, the cross-sectional design of this study precludes the inference of causal relationships as a longitudinal design is required to ascertain directionality and causation (Setia, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Having a diagnosis of ASD in the child is associated with a higher risk of anxiety in caregivers (Zhou et al, 2019 ), compared to other diagnostic groups, as children with ASD may have higher behavioral and more complex developmental challenges. This heightened risk is also seen in various studies as mentioned, both before and during pandemic times, but is especially noticeable among mothers (Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the ASD children depend on lifelong parental care. The mother, being the primary caregiver of the child, is subjected to economic burden and psychological distress 8,9 . Higher levels of anxiety and depression have been reported in mothers of ASD children than in mothers of children with normal development 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…The psychological distress in the mother can lead to compromised child care. Emotional wellbeing helps the mother to deal with the challenges associated with ASD children 8 . Hence, early recognition of emotional disturbance in mothers, and providing them psychological support, results in better care of ASD children.…”
Section: Introductionmentioning
confidence: 99%